Phenoloxidases in Plants—How Structural Diversity Enables Functional Specificity - Blaschek, Leonard; Pesquet, Edouard (Frontiers in Plant Science, 2021)
The metabolism of polyphenolic polymers is essential to the development and response to environmental changes of organisms from all kingdoms of life, but shows particular diversity in plants. In contrast to other biopolymers, whose polymerisation is catalysed by homologous gene families, polyphenolic metabolism depends on phenoloxidases, a group of heterogeneous oxidases that share little beyond the eponymous common substrate. In this review, we provide an overview of the differences and similarities between phenoloxidases in their protein structure, reaction mechanism, substrate specificity, and functional roles. Using the example of laccases, we also performed a meta-analysis of enzyme kinetics, a comprehensive phylogenetic analysis and machine-learning based protein structure modelling to link functions, evolution, and structures in this group of phenoloxidases. With these approaches, we generated a framework to explain the reported functional differences between paralogs, while also hinting at the likely diversity of yet undescribed laccase functions. Altogether, this review provides a basis to better understand the functional overlaps and specificities between and within the three major families of phenoloxidases, their evolutionary trajectories, and their importance for plant primary and secondary metabolism.